IMPLEMENTASI GREEN CHEMISTRY PADA PRAKTIKUM KIMIA DI SMAN 2 REJANG LEBONG - Sura Menda Ginting; Wiwit; Elvinawati; Darwanto Wijaya; Elisabet Vianey (Universitas Bengkulu, 2023)
Community service of Chemistry Education Study Program was conducted in SMAN (senior high school) 2 Rejang Lebong, Bengkulu. This activity aimed to introduce green chemistry-based practicum module in electronic form, with the topic of reaction rate factors and titration reaction using natural indicator. The activities were product introduction, demonstration of using the e-module, discussion, and evaluation toward students’ response of the e-module. The activity was attended by 20 students and three chemistry teachers from SMAN 2. This e-module encouraged schools to conduct chemistry practicum using surrounding ingredients based on green chemistry concept. Students’ response towards e-module showed good response proven by scores gained toward appearance, content, green chemistry aspects, and usability were 80,19%, 82,68%, 94,22%, and 86,63% respectively. Keywords: green chemistry, practicum, community service